2009
DOI: 10.3102/0034654308324653
|View full text |Cite
|
Sign up to set email alerts
|

“But This Story of Mine Is Not Unique”: A Review of Research on African American Children’s Literature

Abstract: This article provides a review of research on African American children’s literature by synthesizing the growing body of textual and reader response research conducted across the past several decades. The literature presented in this article cuts across the disciplines of education as well as English and library science. Using the selective tradition as a theoretical underpinning, the authors review extant literature through a three-pronged thematic heuristic developed as a result of their analysis. These them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 46 publications
(49 reference statements)
1
17
0
Order By: Relevance
“…In his review of popular Western fiction, Marsden (1978) found that frontier literature provided a window into the cultural needs and values of a people who felt compelled to undertake a sizable life change; and this window revealed a fundamental conflict in American culture between the desire for individuality versus the desire to join others in contributing to society. Brooks and McNair (2009) noted that African American children's literature contained narratives that represent an evolution of changing descriptions of African American life and the cultural practices engaged in by its members. This literature depicted the struggles, experiences and aspirations of African Americans and sent messages to comfort African American children so that they could feel good about themselves and their identities.…”
Section: Books As Manifestations Of Societal Valuesmentioning
confidence: 98%
“…In his review of popular Western fiction, Marsden (1978) found that frontier literature provided a window into the cultural needs and values of a people who felt compelled to undertake a sizable life change; and this window revealed a fundamental conflict in American culture between the desire for individuality versus the desire to join others in contributing to society. Brooks and McNair (2009) noted that African American children's literature contained narratives that represent an evolution of changing descriptions of African American life and the cultural practices engaged in by its members. This literature depicted the struggles, experiences and aspirations of African Americans and sent messages to comfort African American children so that they could feel good about themselves and their identities.…”
Section: Books As Manifestations Of Societal Valuesmentioning
confidence: 98%
“…African American children's literature has long been a contested space (Brooks & McNair, ). Both Sims () and McNair () noted a number of issues with children's books featuring African Americans: the misrepresentation of speech patterns, the depiction of whites as active and blacks as passive, and the association of negative traits and ideas as black.…”
Section: Cs: Culturally Relevant Texts Collaboration and Critical mentioning
confidence: 99%
“…Although the comic book/graphic novel format has now become popular in the field of children's literature, few illustrators were using this format in the 1990s. This book is also a piece of fantasy, a genre in which there are few African American children's books (Bishop, 2007;Brooks & McNair, 2009). The paperboy is transformed into a superhero after an encounter with a bird while delivering newspapers on his route.…”
Section: Literary Innovationsmentioning
confidence: 99%